Monthly mean climatology of the prevailing winds and tides in the Arctic mesosphere/lower thermosphere - Portnyagin, Y. I.; Solovjova, T. V.; Makarov, N. A.; Merzlyakov, E. G.; Manson, A. H.; Meek, C. E.; Hocking, W.; Mitchell, N.; Pancheva, D.; Hoffmann, P.; Singer, W.; Murayama, Y.; et al. (Annales Geophysicae, 2004)
The Arctic MLT wind regime parameters measured at the ground-based network of MF and meteor radar stations (Andenes 69° N, Tromsø 70° N, Esrange 68° N, Dixon 73.5° N, Poker Flat 65° N and Resolute Bay 75° N) are discussed and compared with those observed in the mid-latitudes. The network of the ground-based MF and meteor radars for measuring winds in the Arctic upper mesosphere and lower thermosphere provides an excellent opportunity for study of the main global dynamical structures in this height region and their dependence from longitude. Preliminary estimates of the differences between the measured winds and tides from the different radar types, situated 125-273km apart (Tromsø, Andenes and Esrange), are provided. Despite some differences arising from using different types of radars it is possible to study the dynamical wind structures. It is revealed that most of the observed dynamical structures are persistent from year to year, thus permitting the analysis of the Arctic MLT dynamics in a climatological sense. The seasonal behaviour of the zonally averaged wind parameters is, to some extent, similar to that observed at the moderate latitudes. However, the strength of the winds (except the prevailing meridional wind and the diurnal tide amplitudes) in the Arctic MLT region is, in general, less than that detected at the moderate latitudes, decreasing toward the pole. There are also some features in the vertical structure and seasonal variations of the Arctic MLT winds which are different from the expectations of the well-known empirical wind models CIRA-86 and HWM-93. The tidal phases show a very definite longitudinal dependence that permits the determination of the corresponding zonal wave numbers. It is shown that the migrating tides play an important role in the dynamics of the Arctic MLT region. However, there are clear indications with the presence in some months of non-migrating tidal modes of significant appreciable amplitude.